Impact of Guidelines Publication on Acute Bronchiolitis Management: 10-Year Experience from a Tertiary Care Center in Italy - Carlotta Biagi (MDPI AG, 2021)
Bronchiolitis is the most common lower respiratory tract infection in infants. According to evidence-based guidelines, diagnosis is clinical, there is no need for routine use of laboratory or instrumental tests and therapy is primarily supportive, based on oxygen and adequate fluid supplementation. Nevertheless, unnecessary diagnostic tests and pharmacological treatments are still very common. The aim of this retrospective cohort study was to evaluate how the management of bronchiolitis has changed in the last ten years in a Tertiary Care Center in Italy, assessing adherence to national guidelines. Considering the publication of the Italian inter-society consensus document in 2014, we compared patients admitted in the prior four epidemic seasons with patients admitted in the latter six epidemic seasons. The comparison between the two groups showed a significant reduction in the prescription of systemic corticosteroids (58.9% vs. 41.8%, p < 0.001), nebulized epinephrine (73.8% vs. 38.3%, p < 0.001) and antibiotics (59.5% vs. 42.3%, p < 0.001), together with a drastic decrease in the use of chest X-ray (92.2% vs. 54.4%, p < 0.001). On the contrary, the use of inhaled salbutamol remained substantially stable over time (39.4% vs. 37.6%, p = 0.505). Despite the encouraging results, further efforts are needed to limit the prescription of ineffective therapies like antibiotics and inhaled salbutamol.